Update on coupled dark energy and the H0 tension - Gómez-Valent, Adrià; Pettorino, Valeria; Amendola, Luca (Physical review, 2020)
In this work, we provide updated constraints on coupled dark energy (CDE) cosmology with Peebles-Ratra (PR) potential and constant coupling strength beta. This modified gravity scenario introduces a fifth force between dark matter particles, mediated by a scalar field that plays the role of dark energy. The mass of the dark matter particles does not remain constant, but changes with time as a function of the scalar field. Here we focus on the phenomenological behavior of the model, and assess its ability to describe updated cosmological datasets that include the Planck 2018 cosmic microwave background (CMB) temperature, polarization and lensing, baryon acoustic oscillations, the Pantheon compilation of supernovae of Type Ia, data on H(z) from cosmic chronometers, and redshift-space distortions. We also study the impact of the local measurement of H-0 from SH0ES and the strong-lensing time delay data from the H0LICOW Collaboration on the parameter that controls the strength of the interaction in the dark sector. We find a peak corresponding to a coupling beta > 0 and to a potential parameter alpha > 0, more or less evident depending on the dataset combination. We show separately the impact of each dataset and remark that CMB lensing is especially the one dataset that shifts the peak the most towards Lambda CDM. When a model selection criterion based on the full Bayesian evidence is applied, however, Lambda CDM is still preferred in all cases, due to the additional parameters introduced in the CDE model.